Comparison of intra-aneurysmal flow modification using optical flow imaging to evaluate the performance of Evolve and Pipeline flow diverting stents. (21st April 2020) - Cancelliere, Nicole Mariantonia; Nicholson, Patrick; Radovanovic, Ivan; Mendes, Karla Mirella; Orru, Emanuele; Krings, Timo; Pereira, Vitor M
Abstract : Background: Flow diverting stent (FDS) devices have revolutionized the treatment of large and complex brain aneurysms, but there is still room for improvement, particularly on the flow diversion properties and technical challenges associated with stent deployment. In this study we compared flow diversion properties between the new generation Surpass Evolve (Stryker) and the Pipeline Flex (Medtronic) devices by quantitatively evaluating intra-aneurysmal flow modification. Methods: An in vitro experimental set-up was used, consisting of four patient-specific silicone models with internal carotid aneurysms and a circulating hemodynamic simulation system with pulsatile flow. The Evolve and Pipeline stents were deployed across the neck of each aneurysm model, in a randomized fashion, for a total of eight device deployments. A 60 frames/s digital subtraction angiography run was acquired before and after placement of each FDS. An optical flow-analysis method was used to measure intra-aneurysmal flow modification induced by the stent by calculating a mean aneurysm flow amplitude (MAFA) before and after stent placement and computing a ratio. Results: Average MAFA ratio values calculated from pre- and post-stent placement were significantly lower after deployment of the Evolve (n=4, mean=0.62±0.09) compared with the Pipeline device (n=4, mean=0.71±0.06) (p=0.03). Conclusions: Our in vitro results show that the Evolve stent had a superior flow diversion effect compared with the Pipeline stent, which—based on clinical evidence—suggest it may promote faster aneurysm occlusion rates in patients.